2020
DOI: 10.3892/ijmm.2020.4662
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin‑1, a microvascular endothelial‑derived protein, protects against myocardial ischemia‑reperfusion injury (Review)

Abstract: As regards acute myocardial infarction, great success has been achieved in therapies that reduce the effects of myocardial ischemic injury, while few interventions have achieved satisfactory outcomes for myocardial ischemia-reperfusion (IR) injury. Thus, new research is urgently required to achieve breakthroughs in promising treatments. Neuregulin-1 (NRG-1), which is an endothelium-derived protein and the ligand of ErbB receptors, exerts cardioprotective effects and is rapidly upregulated during IR. NRG-1/ErbB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 93 publications
(115 reference statements)
0
7
0
5
Order By: Relevance
“…A member of the epidermal growth factor family, neuregulin-1 (NRG-1) is crucial for the development of cardiomyocytes and cardiac regeneration. There are six isoforms, and each one has an EGF-like domain that is both required and sufficient to activate ErbB receptors and, thus, exerts essential biological activities [ 213 ]. Prior studies have shown the following: NRG1 undertakes anti-fibrotic and anti-remodeling actions in heart failure models, it protects myocardial cells from damage and it improves cardiac function [ 214 ].…”
Section: Resultsmentioning
confidence: 99%
“…A member of the epidermal growth factor family, neuregulin-1 (NRG-1) is crucial for the development of cardiomyocytes and cardiac regeneration. There are six isoforms, and each one has an EGF-like domain that is both required and sufficient to activate ErbB receptors and, thus, exerts essential biological activities [ 213 ]. Prior studies have shown the following: NRG1 undertakes anti-fibrotic and anti-remodeling actions in heart failure models, it protects myocardial cells from damage and it improves cardiac function [ 214 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, activation and agonists of ErbB2 have been proposed as therapeutic approaches for heart disease. ErbB2 overexpression and activator (Neuregulin 1, NRG1) promote cardiac function and repair, particularly in myocardial infarction and heart failure [27,44,45]. More meaningfully, a phase II clinical trial demonstrated that NRG1 effectively improved cardiac function in patients with stable congestive heart failure [46].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ErbB receptors prevents cardiomyopathy [ 132 , 133 ], while their inhibition causes HF in mice [ 134 , 135 , 136 , 137 ]. Neuregulin-1 is mainly synthesized and secreted by endocardial and microvascular endothelial cells in the heart [ 292 ]. Experimental studies and clinical trials demonstrated that recombinant human neuregulin-1 reversed ventricular remodeling and improved cardiac function in subjects with HF [ 293 , 294 , 295 , 296 , 297 ].…”
Section: Emerging Treatment Targeting Specific Mechanisms Of Diabetic...mentioning
confidence: 99%